Nationally Determined Contribution Analysis of Brazil and Some Global North and South Countries - Daniella Ribeiro Pacobello; Samuel Carvalho De Benedicto; Maurício Lamano Ferreira; Cândido Ferreira da Silva Filho; Regina Márcia Longo (Ambiente & Sociedade, 2025)
Abstract The aim of the present study is to analyze Brazil’s Nationally Determined Contribution (NDC) based on the NDCs of countries in the Global North (Germany and United States) and South (China and Namibia). This research is featured by its applied nature, qualitative approach and descriptive goal. According to the study’s results, the assessed countries have taken different actions to reduce GHG emissions by 2030. Some of them have focused some particular sectors in comparison to the others due to their respective main emission sources. Countries in the Global North develop bolder proposals and Brazil is known for being less conservative in proposing targets given its several national emission offset fields; in other words, forest restoration. If commitments in countries’ respective iNDCs are implemented to the letter, it could be enough to reach Target 13.2 of SDG 13.